Deviancy in early Rabbinic literature: a collection of socio-anthropological essays - Fishbane, Simcha (The Brill reference library of ancient Judaism, 2007)
The case of the modified mamzer in early rabbinic texts -- "As the vows of the evil folk" : the structure and implicit message of Mishnah's tractate Nazir -- "In the case of women-any hand which makes many examinations is to be praised" : niddah as viewed by the rabbis of the Mishnah -- "Most women engage in sorcery" : an analysis of female sorceresses in the Babylonian Talmud -- "Go and enjoy your acquisition" : the prostitute in the Babylonian Talmud -- "Hear no evil, speak no evil, see no evil" : the physically handicapped in the Mishnah -- Toward an understanding of the methodology of Mishnah : the case of kutim -- Descriptive or prescriptive : the case of the gentile in Mishnah -- Deviancy in battle : rituals and the Israelite soldier in the Torah and the Mishnah : an anthropological understanding -- "Every dream becomes valid only by its interpretation" : dreams, dream interpretations and dream interpreters in the Babylonian Talmud